ANALISIS e-SERVICE QUALITY TERHADAP e-LOYALTY MELALUI e-CUSTOMER SATISFACTION SEBAGAI MEDIATING PADA PENGGUNA APLIKASI MOST ONLINE TRADING (STUDI KASUS PADA PT XYZ) - Rianto Nurcahyo (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The aim of this study is to find out the indirect influence of service quality on e- loyalty of MOSTOnline Trading users through e-customer satisfaction of PT XYZ. This study is a quantitative research.Methods of data analysis used in this research is Partial Least Square-PLS with SmartPLSapplications. Methods of data collection is using questionnaire which distributed to 162 respondents.The findings suggest that e-service quality has significant effect on e- service customer satisfaction;e-customer satisfaction is positively related to e- loyalty. The findings revealed that there is indirectinfluence between e-service quality and e-loyalty through e-customer satisfaction.